Implementasi Cluster Server Pada Raspberry Pi Dengan Menggunakan Metode Load Balancing - Ryan Ahmadi Putra; Aprianti Putri Sujana (Computer Engineering Departement, Universitas Komputer Indonesia, 2019)
When the server is overloaded, this will make the server slow down, the effect is that the service access time increases which will make the client uncomfortable in using the services that are on the server. Cluster servers offer a solution so that the load is divided evenly, this system utilizes several computers that are configured in such a way that they can work together. The results of cluster server testing show an increase in http request response time by 59% faster than without using a server cluster system. Another advantage of using a cluster server is the existence of redundancy, when one node member is inactive the master node or load balancer will automatically move the request to the active node.